Getting it Right : Creating Partnerships for Change : Integrating Aboriginal and Torres Strait Islander Knowledge in Social Work Education and Practice : Final Report. - Zubrzycki, Joanna; Bessarab, Dawn; Green, Sue; Jones, Victoria; Stratton, Katrina; Young, Susan (Office for Learning and Teaching, 2014)
Final report from a project that was concerned with long term change and curriculum renewal in social work education. The purpose was to make a substantial contribution to the process of Indigenising Australian social work education. In 2011 the Australian Association of Social Work (AASW) released new national educational guidelines aimed at increasing curriculum content in Aboriginal and Torres Strait Islander social work education. These guidelines however, only indicated what values, knowledge and skills need to be taught to students, not how this material might be taught and developed. This project addressed the 'how' by developing learning and teaching strategies to assist the 26 Australian Schools of Social Work to integrate the guidelines into the curriculum.